Effect of different seed deterioration treatments and germination under different temperatures on the activity of antioxidant enzymes and lipid peroxidation in Pumpkin (Cucurbita pepo L.) seedlings - S. Ghahremani; M. Sedghi; R. Seyed Sharifi (علوم و فناوری بذر ایران)
In order to investigate the effects of seed deterioration on the activity of antioxidant enzymes and lipid peroxidation in pumpkin seedlings a factorial experiment conducted based on completely randomized design with three replications. Treatments were three deterioration levels (control, 5 and 10 days deterioration at 45◦C and 95-100% relative humidity) and three germination temperatures (15, 25 and 35°C). Results showed that activity of superoxide dismutase and catalase were the highest at 5 days aging and 25°C, and activity of peroxidase was the highest at non-aging and 25°C. Also, the highest amount of Malondialdehyde (7.1 mmol gr-1FW) observed in the seeds with 10 days deterioration and 15°C. The highest respiration index (0.018 mg) achieved in 5 days deterioration and 35°C and the lowest value (0.009 mg) was related to 10 days deterioration and 35°C. It seems that reduction in seed vigor under deterioration and high temperatures causes to oxidative stress and lipid peroxidation and leads to increase in the activity of antioxidant enzymes in order to face the related damages. Considering results obtained from germination and antioxidant enzymes activity the best temperature for germination of aged seeds of pumpkin was 15◦C.